Integration of gender and youth into Nigerian forestry policy and law instruments- Issues and prospects for sustainable forest management (2018)
Sustainable forest management, when backed with appropriate policy instruments and legal administration will promote improved livelihoods of forest dependants without sacrificing inherited forest biodiversity and its future potential. These are contradictory demands from different stakeholders. While meeting livelihood expectations of forest dependants may seem an affective issue, it may become substantive when their needs are not adequately planned for and they have to meet it within their whims. It may become a social problem. On the other hand maintaining forest biodiversity for posterity may be a substantive issue, the cost may be unbearable in the present. It is against this background that this review was done to analyse policy framework for achieving the socio-economic and ecological cleavage in sustainable forest management in Nigeria, with the view to arriving at international best practices at the nearest opportunity. The review documented the importance of all encompassing tenure arrangement, resource inventory, gender inclusion and youth engagement as pre-requisite to a broad based stakeholder involvement in policy formulation and by engagement sustainable legislation backup, if sustainable forest management is the ultimate goal.